An Audit of Nursing Care and Placement of Peripherally Inserted Central Catheter in Infants - S Rezapour; M Haghshenas Mojaveri; P Aziznejadroshan; K Hajian-Tilaki; S Alizadeh Rokni; T Jahangir (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2023)
Background and Objective: The performance quality of peripherally inserted central catheter (PICC) by nurses has a direct effect on the improvement of patient care and safety. The aim of this study is to audit the placement and nursing care of PICC in infants. Methods: This cross-sectional study was conducted on 130 PICC procedures in the neonatal intensive care units of Rouhani and Amirkola hospitals in Babol in 2018-2021. All infants who needed PICC placement for any reason were selected. In order to collect the data, the observational researcher-made checklist and the infant demographic characteristics questionnaire were used. The checklist included 44 questions and four parts of nursing care before catheter insertion, hand washing, nursing care during the procedure, and nursing care after catheter placement. The scores obtained from the checklist were classified into conversion percentage and two groups of unfavorable placement (less than 67) and favorable placement (68-100). To confirm its reliability, intraclass correlation coefficient was used (ICC=0.90). Findings: A total of 130 cases of PICC placement and nursing care were audited (Rouhani Hospital 98 cases 75.4%, Amirkola 32 cases 24.6%). In the studied sample, 83 (63.8%) were boys and 53 (43.1%) were diagnosed with prematurity. The most common PICC location was the armpit (42.3%). The percentages of compliance of nursing care before PICC insertion according to the standard (97.43%), hand washing (100%), nursing care during the procedure (87.14%) and nursing care after PICC insertion (94.84%) were favorable. Nurses did not use glasses and ultrasound guidance during PICC insertion; (85.4%) and (90%), respectively. Conclusion: According to the results of this study, although the quality of PICC insertion and care in three stages was at a favorable level, nurses need training regarding the use of glasses and ultrasound guidance during PICC insertion.